2013
DOI: 10.1098/rsif.2012.0980
|View full text |Cite
|
Sign up to set email alerts
|

Walking, running, and resting under time, distance, and average speed constraints: optimality of walk–run–rest mixtures

Abstract: On a treadmill, humans switch from walking to running beyond a characteristic transition speed. Here, we study human choice between walking and running in a more ecological (non-treadmill) setting. We asked subjects to travel a given distance overground in a given allowed time duration. During this task, the subjects carried, and could look at, a stopwatch that counted down to zero. As expected, if the total time available were large, humans walk the whole distance. If the time available were small, humans mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 48 publications
(90 reference statements)
3
69
0
Order By: Relevance
“…The sideways walking metabolic rate increased monotonically with speed v (figure 1b). Similar to normal walking [2,4,10], the total sideways walking metabolic rate per unit mass, _ E (including the resting cost), is approximated well, using least squares, by: _ E ¼ a 0 þ a 2 v 2 : For metabolic rate data pooled over the subject population ( figure 1b) . See the electronic supplementary material, S4 for these coefficients' error estimates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sideways walking metabolic rate increased monotonically with speed v (figure 1b). Similar to normal walking [2,4,10], the total sideways walking metabolic rate per unit mass, _ E (including the resting cost), is approximated well, using least squares, by: _ E ¼ a 0 þ a 2 v 2 : For metabolic rate data pooled over the subject population ( figure 1b) . See the electronic supplementary material, S4 for these coefficients' error estimates.…”
Section: Resultsmentioning
confidence: 99%
“…Humans walk and run in a manner that approximately minimizes metabolic energy expenditure [1][2][3][4]. However, most evidence for metabolic energy optimality has been for natural gaits, such as walking and running.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of gait parameters such as average stride length, frequency, and width, there are generally multiple combinations that can satisfy a single goal such as walking speed [1–3]. And for a given speed, it has long been observed that the preferred stride length coincides with minimum metabolic energy expenditure [46].…”
Section: Introductionmentioning
confidence: 99%
“…by avoiding unnecessary high velocities [31,32]. Another possibility to save energy is to take short routes to the destination (see Fig.…”
Section: Preference For the Shortest Pathmentioning
confidence: 99%